PROYECTO DE INVERSIÓN PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE MUEBLES EN MDF PARA NIÑOS EN LA CIUDAD DE LOJA - Granda Dávila, María Fernanda (2016)
This research was developed with the purpose of developing a, INVESTMENT PROJECT FOR THE CREATION OF A COMPANY OF PRODUCER AND MARKETING MDF FURNITURE FOR CHILDREN IN THE CITY OF LOJA. For the development of the research the following methods were used: • The deductive method was used to describe and analyze general concepts company. • The inductive method that served as an important basis for the implementation of surveys yielded information that enabled identify the tastes and preferences of people are and develop the market study. In the market research surveys were applied to buyers and sellers of the city of Loja to determine product acceptance. With this might get the actual demand for 23,910 and 23,757 units unmet demand everything for children in the first year. Subsequently the marketing plan was established by determining the product, price, place and product advertising. On the technical study allowed us to determine the optimal size and location of the company, it is located in the area of the industrial park with an installed production capacity 364 children's furniture. In the project engineering the production process is determined by the development of process flows, machinery and equipment. On the administrative and legal study of the company's organizational principles were defined, its operation as a limited liability company, 5 structural organization and functions manuals. In the study the amount of financial investment and financing required to implement the project, throwing as results for the total project investment amounting to $ 27,608.67 of this amount was determined to be funded $ 19,608.67 with equity and the remaining $ 8,000 00 credit managed by the BNF. Finally, the financial evaluation was performed for which several indicators that showed the following results were analyzed: Net Present Value of $ 9569.92; Internal Rate of Return of 21.94%; Benefit Cost ratio is 1.25 for every dollar invested company earns 0.25 cents; Capital recovery period is 2 years, 9 months and 7 days; Sensitivity analysis indicates that the project supports an increase in the cost of 15.52% for a total of 0.98% and the sensitivity analysis in the decrease in revenues of 12.42% for a total of 0.99%. The conclusions and recommendations indicates that this project is feasible and the bibliography consulted with their respective annexes attached.